Effect of Dietary Supplementation of Lactobacillus Casei YYL3 and L. Plantarum YYL5 on Growth, Immune Response and Intestinal Microbiota in Channel Catfish - Hongyu Zhang; Haibo Wang; Kun Hu; Liting Jiao; Mingjun Zhao; Xianle Yang; Lei Xia (Animals, 2019)
The purpose of this study is to investigate the effect of probiotics L. casei YYL3 (Lc) and L. plantarum YYL5 (Lp) on growth performance, innate immunity, disease resistance and intestinal microbiota of channel catfish. A total of 252 catfish (67.20 ± 1.46 g) were randomly divided into 3 groups which were fed with basal diet, Lc-added (3.0 × 108 cfu/g) or Lp-added (3.0 × 108 cfu/g) diets, respectively. After 4 weeks of feeding, Lc significantly enhanced the growth and feed utilization of channel catfish compared with the control group (CG). Following that, the catfish were challenged with an intraperitoneal injection of 200 μL of the pathogenic E.ictaluri (2.0 × 106 cfu/mL), the relative percent survival of Lc and Lp were 38.28% and 12.76%, respectively. High-throughput sequencing indicated Lc and Lp reduced the alpha diversity of the intestinal microbiota in channel catfish. Lactobacillus were overwhelming in the guts during probiotics treatment, but almost vanished away after 2 weeks post-cessation of probiotics administration. Compared to CG, Lc and Lp resulted in an increased abundance of Pseudomonas and decreased amount of Aeromonas. Functional analysis revealed that Lc treatment upregulated the relative abundance of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways including lipid metabolism, metabolism of other amino acids, metabolism of terpenoids and polyketides, xenobiotics biodegradation and metabolism, and nucleotide metabolism. Combined, our data revealed that Lc, as a feed additive at 3.0 × 108 cfu/g, could promote the growth performance, disease resistance and dramatically change the composition of intestinal microbiota of channel catfish.